TECHNOLOGIES IN HIGHER EDUCATION: PUBLIC POLICIES AND SOCIAL APPROPRIATION OF THEIR IMPLEMENTATION - Melo Fiallos, Diego Fernando (2017)
This paper presents an analysis of the implementation of information and communication technologies in higher education with the aim to contribute knowledge on trends regarding their social appropriation. To that effect, documents of public policies and scientific literature containing guidelines developed by international organizations and explaining different alternatives to guide the process of integrating technologies in education were reviewed. Then, some research works on problems derived from the technology appropriation process without changes in the teachinglearning process are commented. For this, the learning theory of connectivism is discussed as the possible reference framework for this analysis. Findings point to focus attention on learning processes more than on investing in equipment, and highlight the importance of using technologies in education within the context of the fourth industrial revolution in the digital age.